Exposing the myths of household water insecurity in the global north: A critical review. (4th October 2020) - Meehan, Katie; Jepson, Wendy; Harris, Leila M.; Wutich, Amber; Beresford, Melissa; Fencl, Amanda; London, Jonathan; Pierce, Gregory; Radonic, Lucero; Wells, Christian; Wilson, Nicole J.; Adams, Ellis Adjei; et al.
Abstract: Safe and secure water is a cornerstone of modern life in the global North. This article critically examines a set of prevalent myths about household water in high‐income countries, with a focus on Canada and the United States. Taking a relational approach, we argue that household water insecurity is a product of institutionalized structures and power, manifests unevenly through space and time, and is reproduced in places we tend to assume are the most water‐secure in the world. We first briefly introduce "modern water" and the modern infrastructural ideal, a highly influential set of ideas that have shaped household water provision and infrastructure development over the past two centuries. Against this backdrop, we consolidate evidence to disrupt a set of narratives about water in high‐income countries: the notion that water access is universal, clean, affordable, trustworthy, and uniformly or equitably governed. We identify five thematic areas of future research to delineate an agenda for advancing scholarship and action—including challenges of legal and regulatory regimes, the housing‐water nexus, water affordability, and water quality and contamination. Data gaps underpin the experiences of household water insecurity. Taken together, our review of water security for households in high‐income countries provides a conceptual map to direct critical research in this area for the coming years. This article is categorized under: Human Water > Human Water Abstract : "El Río es Para la Gente." A Mural at Manzo Elementary School, Tucson, Arizona, USA (Image source: K. Meehan).